Penampilan dan Keragaman Sifat Kuantitatif Beberapa Aksesi Lokal Kacang Tanah (Arachis hypogaea L.) di Kabupaten Maluku Barat Daya - Lolonlun, Elias; Jambormias, Edizon; Hehanussa, Meitty L; Matatula, Erfina A (Jurnal Agrosilvopasture-Tech, 2025)
Peanuts are a legume with high protein content and an important strategic commodity. Exploration and evaluation of local germplasm to enrich genetic diversity still needs to be carried out for further use in plant breeding programs. One of them is local germplasm in Southwest Maluku Regency (MBD). This research aims to describe the appearance and diversity of agronomic traits of several local peanut accessions from Southwest Maluku. The research will take place from November 2022 to February 2023 at the Moa Nursery UPTD, MBD Regency. The design used was a completely randomized block design with a Variety factor consisting of 5 levels, and each level was repeated three times. The variety factor consists of four local accessions and one national superior variety, namely Tasia 2. The analysis used is analysis of variance between accessions and within accessions. If there is an influence of accessions, the analysis is continued with the Duncan Multiple Distance Test (UJBD), and evaluation of diversity in accessions uses descriptive analysis with boxplot graphs. UJBD shows that the growth of local accessions is relatively the same as the superior variety Tasia 2, and the production of the Putih Leti and Putih Kisar accessions is higher than Tasia 2. Boxplot analysis shows that the accessions Putih Kisar, Merah Leti, Putih Leti and Merah Kisar show diversity in plant height and number of productive branches.